INDIVIDUAL COUNSELING WITH THOUGHT STOPPING TECHNIQUES TO OVERCOME SUICIDAL THOUGHTS : CASE STUDY OF LATE ADOLESCENT "T" IN MARIANA LAMENT - Bleyzenky, Ikke; Noviza, Neni; Fitri, Hartika Utami (Jurnal Konseling Pendidikan Islam, 2025)
Overcoming Suicidal Thoughts (Case Study of Late Adolescent "T" in Mariana Village). Which aims to determine the description of suicidal thought and to determine the application of individual counseling using the thought-stopping technique in overcoming suicidal thought in late adolescents. The type of research is field research with a qualitative approach and case study method, where researchers will dig up information in depth from several sources. Data collection techniques used are observation, interviews, and documentation. The data analysis techniques used in this study are pattern matching, data explanation, and time series analysis. The results of this study indicate that after carrying out the counseling process, as many as 4 meetings in one month were conducted using several stages of counseling implementation, namely, the initial stage, the activity stage, and the final stage. In this process, it can be seen that during individual counseling by applying the thought stopping technique, there are several changes in the behavior of client "T" where they are wiser in controlling themselves in a more positive way.